Production and characterisation of xylan degrading enzymes produced from Penicillium chrysogenum using agricultural biomass - Ullah, Sadia Fida (2019)
Tese (doutorado) — Universidade de Brasília, Instituto de Ciências Biológicas, Departamento de Biologia Celular, Programa de Pós-Graduação em Biologia Molecular, 2019.